Accurate low-dose iterative CT reconstruction from few projections by Generalized Anisotropic Total Variation minimization for industrial CT - Debatin, Maurice; Hesser, Jürgen (Journal of X-ray science and technology, 2015)
BACKGROUND: Reducing the amount of time for data acquisition and reconstruction in industrial CT decreases the operation time of the X-ray machine and therefore increases the sales. This can be achieved by reducing both, the dose and the pulse lengt